Samodzierżawie - Chojnicka, Krystyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This article is showcasing the lasting nature of tsarist samoderzhaviye often translated into English as ‘tsarist autocracy’. It proposes atypology based on principal characteristics of this phenomenon — both those widely accepted and those not included in different definitions offered by existing accounts. To discuss disagreements in the literature, such as temporal boundaries of this form of government, historical judicial acts are considered, which is anovel addition to the literature. This allows the author to reconstruct the historical, official conceptualizations of this form of government. The article also compares samoderzaviye with other forms of totalitarian and autocratic government.
Keywords: Rosja; władza; samodzierżawie; absolutyzm; totalitaryzm; autorytaryzm